"Choking without killing": Opacity and the grey area of migration governmentality. (August 2021) - Tazzioli, Martina
Abstract: This paper focuses on the "grey area of migration governmentality" by dealing with modes of border violence which are opaque and remain under the threshold of political visibility and that, however, highly disrupt and hamper migrants' lives and movements. It starts by conceptualising the notion of "grey area" by building on scholarship that questions the biopolitical formula "making live/letting die" highlighting modes of governing migration through choking and injuring. Building on that, the paper shows that the grey area consists of heterogenous political technologies that choke migrants and disrupt their infrastructures of liveability. In light of that, it moves on by analysing how migrants across Europe are contained and governed by being choked and cramped, with a specific focus on Calais and Ventimiglia. The third section shows that to be disrupted are not only migrants' but also their infrastructures of liveability: migrants are hampered from building collective spaces of life. In the last part, the article comes to grips with opacity as a constitutive feature of the grey area of governmentality, analysing how this is played out both in local decrees and through police tactics.